Video-Assisted Thoracoscopic Lung Biopsy in Critically Ill Patients With Hematologic Malignancy and Acute Respiratory Distress Syndrome: A Case Series Report - Elizabeth Arrieta MD; Saveria Sangiovanni MD; Juan Esteban Garcia-Robledo MD; Mauricio Velásquez MD; Luz Fernanda Sua MD, PhD; Liliana Fernández-Trujillo MD (SAGE Publishing, 2020)
Pulmonary complications are prevalent among patients with hematologic malignancies, who are at high risk of developing acute respiratory distress syndrome (ARDS). Although diffuse alveolar damage is considered the diagnostic hallmark of ARDS, there are plenty of other non-diffuse alveolar damage etiologies that can mimic ARDS and benefit from a specific therapy, therefore correcting the underlying cause. When the etiology remains unclarified despite noninvasive procedures, a surgical lung biopsy (either open via thoracotomy or video-assisted thoracoscopic surgery [VATS]) may be warranted. However, the role of surgical lung biopsy has not been extensively studied in patients with hematologic malignancy and ARDS and so doubt exists about the risk-benefit relationship of such procedures. In this article, we report a series of 8 critically ill patients with hematologic malignancies and ARDS, who underwent VATS lung biopsy, in a specialized institution in Cali, Colombia, from 2015 to 2019, with special emphasis on its diagnostic yield, modifications in treatment protocol, and safety. VATS lung biopsy is a minimally invasive procedure that appears to be a relatively safe with few postoperative complications and minimal perioperative mortality. It has a high diagnostic yield, resulting in a modification of treatment in a nondepreciable percentage of patients. However, this subset of patients was critically ill, with a high risk of mortality, and the lung biopsy did not appear to affect in this aspect. Future randomized controlled trials are needed to further clarify this topic.